Alum catalyzed convenient synthesis of quino [2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives - Sonar, Swapnil S.; Sadaphal, Sandip A.; Shitole, Nana N.; Jogdand, Nivrutti R.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Bulletin of the Korean Chemical Society, 2009)
We have described an efficient synthesis of quino[2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives by the nucleophilic addition of triethyl phosphite to substituted quino[2,3-b][1,5]benzoxazepines promoted by easily available, inexpensive and mild catalyst KAl(SO(4))(2)center dot 12H(2)O (alum). The reactions proceed smoothly at room temperature under solvent-free reaction conditions and providing high yield of product in very short reaction time.
Keywords: 5]benzoxazepine; alpha-Aminophosphonate; Alum; Quino[2.3-b][1; Solvent-free; Triethyl phosphite

Microwave assisted convenient synthesis of quino[2,3-b][1,5]benzoxazepines - Sonar, Swapnil S.; Sadaphal, Sandip A.; Pawar, Shivaji S.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
A convenient synthesis of quino[2,3-b][1,5]benzoxazepines from substituted 2-chloroquinoline-3-carbaldehyde and 2-hydroxyaniline by using stable, non-toxic and inexpensive catalyst 1,8-diazabicyclo-undecan-7-ene (DBU)/silica gel is described. This method affords the quino[2,3-b][1,5]benzoxazepines under the influence of microwave irradiation (360 W) in solvent-free conditions within short reaction times (2-3 min), giving high yields of products (93-96%). (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: 3-b][1; 5]benzoxazepines; DBU/silica gel; Microwave irradiatiom; Quino[2; Solvent-free